A Challenging Case of Solitary Necrotic Nodules of the Liver Mimicking Hepatic Metastases: CT, MRI, and PET-CT Findings - Ji Yeon Hwang; Ji Eun Lee; Min Jung Jung (Journal of the Belgian Society of Radiology, 2020)
Main teaching point: Solitary necrotic nodules of the liver can be multiple and usually appear as hypovascular nodules mimicking hepatic metastases, but they are relatively small and located in the subcapsular areas of the liver. We report a very rare case of multiple solitary necrotic nodules of the liver mimicking hepatic metastases in a patient with previous history of lung cancer. The lesions appeared as low-attenuated or low-signal intensity nodules with thin rim enhancement on both contrast-enhanced computed tomography (CT) and magnetic resonance (MR) imaging, making them difficult to differentiate from hepatic metastases. This rare benign entity should be kept in mind, especially when lesions are small and located in the subcapsular areas of the liver.